Optimizing the Enzymatic Elimination of Clogging of a Microfiltration Membrane by Parellada Grape Cake. Issue 2 (5th March 2015) - Pagán, Jordi; Conde, Josep; Echavarría, Ana Paola; Ibarz, Albert
Abstract: Clogging of the filtration membranes is one of the main problems in the process of obtaining grape must for white wine; therefore, clogging must be reduced to the maximum. The aim of this work was to find the optimal values of the temperature, time and enzyme solution concentration variables to know the best conditions to reduce the clogging of P arellada var. grape pulp in microfilters by enzymatic hydrolysis. Moreover, a study of the effluents produced in this process was also carried out. The unclogging experiments carried out at different temperatures and times led to the activation energy value of 60.3 kJ/mol, and the optimum conditions obtained, those that produced the best filtration, were temperature of 51.8C, time of 35 min and enzyme solution concentration of 379.4 μ L/L. Finally, the kinetic equations of the variation in the contents of the effluents generated in this process under the optimal conditions were also determined. Practical Applications: This paper shows an application of a new original funnel reactor designed by the authors to remove the clogging by enzymatic digestion where the experimental parameters of the filtration process can be varied in order to achieve the optimal values of these parameters to improve the efficiency of the process. Using the values obtained for the process variables, a significant reduction of economic costs could be obtained compared with non‐optimized cake degradation, particularly which produced a decrease in the dose of the added enzyme, whose relationship with the amount of pulp in the filter will not change in the scaling up of the process.